The Association between Lifestyle and Nutritional Status with the Incidence of Hypertension in the Kayu Manis Community Health Centre Working Area - Indriya Rahmadhona Pratiwi; Muh. Guntur Sunarjono Putra; Asri Ismiyani Nurlita; Dwikani Oklita Anggiruling (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Hypertension was a non-communicable disease that contributed to high mortality rates, with cases continuing to increase, including in the working area of the Kayu Manis Community Health Centre, Bogor City. This study aimed to analyze the association between lifestyle, and nutritional status with the incidence of hypertension. This study used a cross-sectional design with 76 subjects aged 30-49 years using purposive sampling techniques. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ). High sodium and fat consumption habits were assessed using the FFQ questionnaire, while smoking, alcohol, and coffee consumption habits were assessed through interviews using questionnaires. Nutritional status was assessed using anthropometric measurements consisting of weight and height measurements. Data were processed and analyzed using Microsoft Excel 2019 and SPSS 26 for Windows. The statistical test used is the Spearman test. The results showed a significant association between physical activity (p=0.002), sodium consumption (p=0.002), fat consumption (p=0.004), and nutritional status (p=0.003) with the incidence of hypertension. Conversely, no significant association was found in the frequency of alcohol and coffee consumption, and duration of smoking. The implications of these findings required lifestyle modification interventions.